2023
DOI: 10.36596/jpkmi.v4i1.602
|View full text |Cite
|
Sign up to set email alerts
|

Edukasi Kendalikan Tekanan Darah dengan Menerapkan Gaya Hidup Sehat di RW 11 Kelurahan Sukamentri Garut

Abstract: Abstrak: Faktor-faktor penyebab tekanan darah tinggi diantaranya umur, jenis kelamin, keturunan, merokok, asupan garam berlebih, konsumsi lemak, minyak goreng bekas, kebiasaan minum alkohol, berat badan berlebih,  aktivitas fisik kurang, stres dan penggunaan estrogen. Semua ini terkait dengan gaya hidup yang tidak sehat.  Faktor resiko tersebut dapat dihindari dengan melakukan upaya-upaya preventif diantaranya dengan menerapkan pola hidup sehat, seperti minum obat rutin dan kontrol tekanan darah. Melalui penge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The results of the community service carried out (Sumarni, Rosidin, Sumarna, & Sholahudin, 2021) are in line with this activity with the pre-test which consisted of 10 questions, the smallest score was 55.2 and the largest score were 65, and the post-test results obtained the smallest score of 78.4 and the largest 85.2. So, it was found that through health education to the elderly, they understand and know the importance of elderly exercise to improve body fitness.…”
Section: The Mean Decrease In Blood Pressure Before and After The Imp...supporting
confidence: 68%
“…The results of the community service carried out (Sumarni, Rosidin, Sumarna, & Sholahudin, 2021) are in line with this activity with the pre-test which consisted of 10 questions, the smallest score was 55.2 and the largest score were 65, and the post-test results obtained the smallest score of 78.4 and the largest 85.2. So, it was found that through health education to the elderly, they understand and know the importance of elderly exercise to improve body fitness.…”
Section: The Mean Decrease In Blood Pressure Before and After The Imp...supporting
confidence: 68%